UTANG LUAR NEGERI INDONESIA ( Perspektif Ekonomi Politik ) - Manoppo, Viviane (Journal of Indonesian Applied Economics, 2007)
The emerging of foreign debt is caused by the inability of domestic fund in financingproject which can increase national product. Foreign debt has a great potential indrowning  developing  countries  since  the  aims  of  donor  countries  and  recipientcountries are not always  the  same and perhaps  even  in  contradictory since eachcountry has its own agenda. In fact, the issue of foreign debt in Indonesia has beenslightly felt seriously after net transfer of  the capital out since 1985. Nett transferhappens if foreign debt repayment is greater than the number of new debt in eachyear. In other words, net resource transfer is getting higher.Keywords: foreign debt, developing countries,transfer